Genetic diversities and historical dynamics of native Ethiopian horse populations (Equus caballus) inferred from mitochondrial DNA polymorphisms - Effa, K.; Rosenbom, S.; Han Jianlin; Dessie, Tadelle; Beja-Pereira, A. (MDPI, 2021)
Matrilineal genetic diversity and relationship were investigated among eight morphologically identified native Ethiopian horse populations using polymorphisms in 46 mtDNA D-loop sequences (454 base pairs). The horse populations identified were Abyssinian, Bale, Borana, Horro, Kafa, Kundido feral horses, Ogaden and Selale. Mitochondrial DNA D-loop sequences were characterized by 15 variable sites that defined five different haplotypes. All genetic diversity estimates, including Reynolds’ linearized genetic distance, genetic differentiation (FST) and nucleotide sequence divergence (DA), revealed a low genetic differentiation in native Ethiopian horse populations. However, Kundido feral and Borana domestic horses were slightly diverged from the rest of the Ethiopian horse populations. We also tried to shed some light on the matrilineal genetic root of native Ethiopian horses from a network constructed by combining newly generated haplotypes and reference haplotypes deposited in the GenBank for Eurasian type Turkish Anatolian horses that were used as a genetic conduit between Eurasian and African horse populations. Ninety-two haplotypes were generated from the combined Ethio-Eurasian mtDNA D-loop sequences. A network reconstructed from the combined haplotypes using Median-Joining algorithm showed that haplotypes generated from native Ethiopian horses formed separate clusters. The present result encourages further investigation of the genetic origin of native African horses by retrieving additional mtDNA sequences deposited in the GenBank for African and Eurasian type horses.